Competitive devaluations in commodity-based economies: Colombia and the Pacific Alliance Group - Guglielmo Maria Caporale; Rodrigo Costamagna; Gustavo Rossini (Deutsches Institut für Wirtschaftsforschung (DIW), 2016)
This paper investigates whether there is an S-Curve in Colombia using bilateral and disaggregated quarterly data for the period 1991-2014. More precisely, the short-run effects of a depreciation on the TB are analysed in 27 industries covered by the PAG Free Trade Agreement. The S-Curve found in sectors representing 30% of total industrial production suggests that in these cases competitive devaluations have a positive effect on the TB in the short run. However, the regression analysis using both OLS and FE methods shows that sizable ones are needed to produce the desired effects on trade flows. Our findings have important policy implications: since only large competitive devaluations can restore TB equilibrium, industrial restructuring would appear to be a more sensible strategy, though this cannot be achieved in the short run and is instead a medium/long-term goal.
Keywords: F1; F4; O1; 330; Devaluations; Trade balance; S-Curve; PAG Free Trade Agreement